6(2,4-Dichlorophenoxy)dibenzo[d,f][1,3,2]dioxa-phosphepine-6-sulfide - Krishnaiah, M.; Babu, V. H. H. Surendra; Krishna, J. R.; Kumar, K. A.; Reddy, C. S.; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2005)
In the title compound, C18H11Cl2O3PS, the seven-membered phosphepine ring exhibits a distorted-boat conformation, with the phosphoryl sulfide group axial and the dichlorophenoxy group equatorial. Fusion of the phosphepine ring to the biphenyl system causes strain, as evidenced by both widening and compression of the endocyclic angles in the heterocyclic ring. The P=S bond length is 1.8939 (12) angstrom and the planar dichlorophenyl ring is oriented at an angle of 28.70 (6)degrees to the phosphepine ring.

Diethyl [(5-chloro-2-hydroxyanilino)(4-chlorophenyl)methyl]phosphonate - Krishnaiah, M.; Babu, V. H. H. Surendra; Prasad, G. Syam; Reddy, C. Suresh; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2009)
In the title compound, C17H20Cl2NO4P, the P atom is bonded in a distorted tetrahedral environment. The dihedral angle between the two benzene rings is 80.5 (1)degrees. In the crystal structure, intermolecular O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds link pairs of molecules into centrosymmetric dimers. These dimers, are in turn, linked by weak intermolecular C-H center dot center dot center dot O hydrogen bonds into one-dimensional chains along [010]. Additional stabilization is provided by very weak C-H center dot center dot center dot Cl interactions.